Análise de desempenho de sistemas distribuídos de grande porte na plataforma Java - Lima, Gleydson de Azevedo Ferreira (2007)
The lava Platform is increasing1y being adopted in the development of distributed sys¬tems with higb user demando This kind of application is more complex because it needs beyond attending the functional requirements, to fulfil1 the pre-established performance parameters. This work makes a study on the Java Vutual Machine (JVM), approaching its intemal aspects and exploring the garbage collection strategies existing in the literature and used by the NM. It also presents a set of tools that helps in the job of optimizing applications and others that help in the monitoring of applications in the production envi¬ronment. Doe to the great amount of technologies that aim to solve problems which are common to the application layer, it becomes difficult to choose the one with best time response and less memory usage. This work presents a brief introduction to each one of tbe possible technologies and realize comparative tests through a statistical analysis of the response time and garbage collection activity random variables. The obtained results supply engineers and managers with a subside to decide which technologies to use in large applications through the knowledge of how they behave in their environments and the amount of resources that they consume. The relation between the productivity of the technology and its performance is also considered ao important factor in this choice